Treatment and Experimental Infection with Klebsiella pneumoniae in Rats - Aqeel A. Alsadawi1, Dhuhah Hayder Abdul-Jawad1, Noor Hani AL-Naji1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
So many diseases are caused by Klebsiella species including urinary tract infections (UTIs), pneumonia, sepsis, diarrhea and bacteremia. Also Klebsiella is responsible for a significant number of community-acquired infectionssuch as pneumonia that results in severe injury in the lung and responsible for a high death ratein children. The intranasal and left lung route of K. pneumoniae infection causes pathological change in the lungs tissues due to acute and chronic injury. Conducted to detect the histological and immunological changes in experimental rat’s lung infected by different routes with K.pneumoniae.Twenty-sevenAlbino Swiss male rats (Rattus rattus) were infected with 0.2ml of K. pneumonia suspension in different routes. After seven days from the last injection K.pneumoniae, the Lung and spleen are examined for histopathology changes. The blood vessels congestion with dispersed lymphocytic cells, infiltration throughout pulmonary parenchyma parts, edema formation along with hemorrhages Early neutrophils distribute into the Broncho-alveolar space, were detected. An acute splenitis was present in rat’s infection by left lung injection route after 10days, were observed in the Spleen tissue with mild white pulp within pulp hyperplasia.What makes K. pneumoniae infections more difficult to treat is that they gradually became more virulent and antibiotic resistant through time.The early K. pneumoniae infection -induced secretion of tumor necrosis factor alpha as pro-inflammatory cytokines.The level of cytokines has been related to severity of pulmonary inflammatory process.TNF-?is important for the acute phase response as proinflammatory responses.